Impact of Government Grant on Financing Students Loan at Higher Learning Institution in Zanzibar - Abeid, Raya Ali; Hamad, Abdalla Ussi (RA Journal of Applied Research, 2022)
The main concern of this study was to examine the impact of government grant on financing students’ loan at higher learning institution in Zanzibar. The researcher has mainly employed quantitative research approach with appropriate method of analysis for this study. The sample size for this study consists of 38 respondents and survey questionnaire was used as data collection instrument. To achieve a reliable study a regression analysis was used to analyses the collected data from relevant respondents. The study has revealed that both amount of grant allocated and fund availability had a significant contribution on the outcome variable (financing student loan). The study concluded that the number of students’ graduates in higher learning institutions in Zanzibar has increased as a result of the availability of students’ aids through students’ loans and guidelines and criteria for granting loans are agreeable hence they are favorable to loans beneficiaries. Finally, the study recommended that the ZHESLB should grant loan to all students who need it without considering their courses or employment status and the guidelines and criteria for granting loans should be improved to include the assessment of economic status of students’ loans applicants.